Analysis of Students' Metacognition Skills in Problem Solving Viewed from Extrovert Personality Types - Fenty Madelin Madubun; Wilmintjie Mataheru; Christina Martha Laamena (Universitas Negeri Makassar, 2023)
Metacognition skills, namely planning, monitoring, and evaluation. The purpose of this study was to describe the metacognition of junior high school students in solving problems of extroverted personality types in the matter of a system of two-variable linear equations. This type of exploratory research with a qualitative approach. The subjects consisted of 2 junior high school students with extroverted personality types. Data collection techniques were carried out using personality type questionnaires, tests, and interviews. The research instrument consisted of a personality type questionnaire, test questions and interview guidelines. Data analysis techniques, namely data reduction, data presentation and drawing conclusions. The results showed that the metacognition skills of the two subjects were different in solving problems. S1 and S2 subjects are aware of the planning process by using prior knowledge that can help them solve problems, determine what is known and asked correctly. In the monitoring process, the S1 subject can think of several strategies or methods, carry out the correct completion steps, and re-check the calculations made, whereas the S2 subject is less aware of the mistakes made in the steps of working on the problem he is doing. In the evaluation stage, the S1 subject evaluates the strategy, work steps or calculations in accordance with the objectives of the problem and draws the correct conclusions, while the S2 subject makes mistakes in the steps of working on the problem that he is not aware of and draws conclusions that are not correct.